Advances in Oligosaccharides and Polysaccharide Modifications in Marine Bioresources - Kumagai, Yuya; Kishimura, Hideki; Zhu, Benwei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Due to global climate change, environmental issues have become more conscious. Seaweeds play a major role in blue carbon, which fixes carbon to the ocean by taking in carbon dioxide through photosynthesis and producing polysaccharides. In addition to environmental problems, marine polysaccharides have various modifying groups and have been found to have different functionality from land plants. Marine polysaccharides have been used in foods and medicines. Recently, novel biocatalysis of polysaccharide-relating enzymes has been discovered. As a result, the functionality of oligosaccharides from marine polysaccharides has been clarified, e.g., health functionality such as anti-cancer, anti-inflammatory effect, intestinal regulation and antioxidant activity. This Special Issue aims to accumulate the knowledge of preparation, function, structure, and application of bioactive oligosaccharides and polysaccharides-relating enzymes from marine organisms. This Special Issue aimed to contribute to the achievement of multiple goals of Sustainable Development Goals (SDGs) (No. 2, 3, 12, 14), and we invited scientists to submit their latest research findings in this field. Comprehensive review papers are also welcomed.